Cerebral damage in diving: Taking the cue from sports concussion medicine - Shuttleworth-Edwards, AB; Whitefield-Alexander, VJ (South African Journal of Sports Medicine, 2012)
Within the compressed gas diving arena there is a risk of cerebral damage with deleterious neuropsychological sequelae in association with decompression illness (DCI), hypoxia, gas toxicity, as well as the cumulative subclinical effect of ‘silent’ paradoxical gas embolisms, the last being an area of growing concern. However, within diving medicine there is little evidence of the regular use of neuropsychological evaluation to monitor brain-related sequelae of frequent diving activity. In contrast, in recent years there has been an explosion of interest in the management of sports concussive injury, including emphasis on the pivotal role of neuropsychological evaluation within that context. Taking the cue from sports concussion medicine, it is proposed that there is an urgent need to incorporate neurocognitive baseline and follow-up screening as a core component in the medical management of those involved in intensive commercial and recreational compressed air diving activities. The objective would be to facilitate (i) accurate neurodiagnostic follow-up of frank DCI or an identifiable hypoxic or toxic incident; (ii) timeous identification of cumulative deleterious effects of repetitive subclinical hypoxic/toxic incidents and/or ‘silent’ paradoxical gas embolisms that might affect them in later life; and (iii) disability assessment following any such events or the combination thereof for rehabilitation and compensation purposes.